Desenvolvimento dos músculos do peito e dos ossos de membro pélvico em codornas europeias e japonesas - Figueroa, Christian Douglas Nichele (2016)
The objective was to study the development of breast muscles and the long bones of the hindlimb in European and Japanese quails. In Experiment I the growth and growth rates of breast and their muscles were described, as their morphological development and meat quality. Embryos with 13 and 15 days of incubation were used, of quail chicks at hatch and at 4, 7, 10, 14, 21, 28 and 35 days (n = 60). The meat quality was evaluated at 35 days for male and female (n = 30), European and Japanese quails. The variables were evaluated by Gompertz equation. The European quails were precocious in relation to Japanese, with maximum growth rate at 16 and 19 days, respectively. However, regarding muscle growth, both types of quails showed maximum growth rate to the breast at day 21. The supracoracoideus muscle showed higher growth rate compared to the pectoral muscle, although the pectoral muscle has represented most of the breast weight. The diameter of muscle fiber type IIa and IIb, classified with the NADH-TR technique, of the pectoral muscles and supracoracoideus in both quails increased over the days of age, showing that the largest increases were the fibers belonging to the pectoral muscle. The frequency of muscle fiber type IIa and IIb of the pectoral and supracoracoideus muscles differed between the quails increasing with quadratic behavior, depending on age. The amount of muscle fibers type IIb in supracoracoideus muscle showed interaction between the type and days of age, with decreasing quadratic behavior. European quails had higher relative breast weight and higher L * (lightness index). Japanese quail showed higher value for a* (red intensity), featuring darker muscles. Regarding gender, male quails showed higher value of b * (yellow intensity). For pH and water retention capacity of the chest muscles there was no significant effect of sex or type of quails. In Experiment II the objective was to describe the growth and morphometric properties, biomechanics, bromatological, histological and chemical characteristics of the long bones (femur, tibiotarsus and tarsometatarsus) in European and Japanese quail, at the end of the incubation to 35 days of age. Embryos with 13 and 15 days of incubation were used, of quail chicks at hatch and at 4, 7, 10, 14, 21, 28 and 35 days (n = 60). The bones were weighed and submitted to a computed tomography cone beam to determine the bone density in Housnfield scale, volume and morphometric analysis as length, thickness and diameter of the shaft. After that the Seedor index was determined, the breaking strength, the cross sectional area, the mineral content, and the percentage of calcium, phosphorus and magnesium. In the left tibiotarsus the thickness of epiphyseal cartilage was determined. The variables weight of the quails and weight, length, Seedor index, volume, thickness and diameter of the shaft of the assessed bone and mineral matter of tibiotarsus were adjusted to Gompertz curves. For the femur and tibiotarsus the variables showed differences in the rate and weight at maturity and period in which the rate was highest, indicating distinct growth of the bones. However tarsometatarsus presented different weight to maturity. With the derivative of Gompertz equation it was observed that in the European quails the growth of tibiotarsus happens first in relation to the thickness of diaphyseal and after in length. The opposite occurred in Japanese quails. For bone density, cross-sectional area there was interaction between the types of quails and days of age, with cubic behavior, and in European quail bones showed to be more dense than Japanese. The bone strength increased linearly in the femur and tibiotarsus and had increasing quadratic behavior in tarsometatarsus with age. The percentage of magnesium and the thickness of the epiphyseal cartilage had a cubic effect over age. Calcium percentage showed no significant differences. We conclude that European and Japanese quails have a different development of chest muscles and that the growth of tarsometatarsus bone showed similarities compared between European and Japanese quails, however, the femur and tibiotarsus have major differences in growth, especially in the 1st days post-hatching.